The founding fathers : creators of the United States - Malam, John, 1957- (Scholastic Inc., 2014)
From the Declaration of Independence to the Louisiana Purchase, the United States of America was shaped by the work and ambitions of some of the greatest political minds and strongest leaders the world has ever seen. This book investigates the lives and influence of the Founding Fathers of the United States, and the lasting impact they have to this day.